2007
DOI: 10.1086/519459
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Regression, and the Allometry of Physiological Traits

Abstract: Physiological and ecological allometries often pose linear regression problems characterized by (1) noncausal, phylogenetically autocorrelated independent (x) and dependent (y) variables (characters); (2) random variation in both variables; and (3) a focus on regression slopes (allometric exponents). Remedies for the phylogenetic autocorrelation of species values (phylogenetically independent contrasts) and variance structure of the data (reduced major axis [RMA] regression) have been developed, but most funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 40 publications
(59 reference statements)
2
35
0
Order By: Relevance
“…We do not take a model fitting approach here because the available methods do not seem biologically relevant, and because they require the assertion of even more as yet unsubstantiated assumptions. In simulations where the exact timings of evolutionary divergences (ancestral nodes) and character states were known, and different rates of evolution were applied, the Felsenstein (1985) PIC method was found to correlate most closely with true contrast values (O'Connor et al, 2007; Sieg et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…We do not take a model fitting approach here because the available methods do not seem biologically relevant, and because they require the assertion of even more as yet unsubstantiated assumptions. In simulations where the exact timings of evolutionary divergences (ancestral nodes) and character states were known, and different rates of evolution were applied, the Felsenstein (1985) PIC method was found to correlate most closely with true contrast values (O'Connor et al, 2007; Sieg et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Because shared evolutionary history among species can cause interspecific trait similarity, it may inflate statistical power in comparative analyses, possibly leading to erroneous conclusions [23,24,98,99]. Nevertheless, current methods for accounting for phylogenetic autocorrelation in comparative studies (e.g., PGLS) are not a panacea for resolving these issues because (1) most phylogenies are incomplete and include unresolved relationships (‘soft’ polytomies), and (2) specific models of trait evolution, such as Brownian motion, must be assumed to perform the analyses, yet are not empirically supported [100].…”
Section: Methodsmentioning
confidence: 99%
“…The problem also potentially applies to intraspecific studies of related individuals because closely related individuals are more likely to be similar that distantly related ones, though this is rarely acknowledged except in quantitative genetic studies that partition phenotypic variation into genetic and other components (106,243; see also 153 for a demonstration of the link between quantitative genetic and comparative analyses). Violation of the assumption of independence in interspecific analyses leads to inflated degrees of freedom, increased Type I error rates, overestimation of the strength of regression relationships, and a significant increase in the variance of the scaling exponent estimate (119,125,160,295,343). Blomberg et al (34) have shown that for studies with 20 or more species, most traits show significant phylogenetic signal, defined as the tendency for related species to resemble each other.…”
Section: Phylogenetic Signal In Interspecific Scalingmentioning
confidence: 99%